Highly conserved motifs within the large Sec7 ARF guanine nucleotide exchange factor GBF1 target it to the Golgi and are critical for GBF1 activity - Pocognoni, Cristián Adrián (2018)
Cellular life requires the activation of the ADP-ribosylation factors (ARFs) by Golgi brefeldin A-resistant factor 1 (GBF1), a guanine nucleotide exchange factor (GEF) with a highly conserved catalytic Sec7 domain (Sec7d). In addition to the Sec7d, GBF1 contains other conserved domains whose functions remain unclear. Here, we focus on HDS2 (homology downstream of Sec7d 2) domain because the L1246R substitution within the HDS2 α-helix 5 of the zebrafish GBF1 ortholog causes vascular hemorrhaging and embryonic lethality (13). To dissect the structure/function relationships within HDS2, we generated six variants, in which the most conserved residues within α-helices 1, 2, 4, and 6 were mutated to alanines. Each HDS2 mutant was assessed in a cell-based “replace-ment” assay for its ability to support cellular functions normally supported by GBF1, such as maintaining Golgi homeostasis, facilitating COPI recruitment, supporting secretion, and sustaining cellular viability. We show that cells treated with the pharmacological GBF1 inhibitor brefeldin A (BFA) and expressing a BFA-resistant GBF1 variant with alanine substitutions of RDR1168 or LF1266 are compromised in Golgi homeostasis, impaired in ARF activation, unable to sustain secretion, and defective in maintaining cellular viability. To gain insight into the molecular mechanism of this dysfunction, we assessed the ability of each GBF1 mutant to target to Golgi membranes and found that mutations in RDR1168 and LF1266 significantly decrease targeting efficiency. Thus, these residues within α-helix 2 and α-helix 6 of the HDS2 domain in GBF1 are novel regulatory determinants that support GBF1 cellular function by impacting the Golgi-specific membrane association of GBF1.